Structural studies of the perovskite series La1−xSrxCoO3−δ during chemical looping with methane. Issue 34 (10th April 2019) - Li, Tianyu; Jayathilake, Rishvi S.; Taylor, Daniel D.; Rodriguez, Efrain E.
Abstract : Perovskite oxides are promising materials as oxygen carriers in chemical looping applications. Abstract : Perovskite oxides are promising materials as oxygen carriers in chemical looping applications. We analyze in situ X-ray diffraction data on the perovskite phases La1− x Sr x CoO3− δ for x = 0, 0.25, 0.5, and 0.75 under chemical looping conditions. We report and discuss their structural evolution, cycling stability, and suitability as oxygen storage materials.